2014
DOI: 10.1097/nna.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Contributions to Chronic Disease Management in Primary Care

Abstract: There is the potential to optimize and standardize the nursing role within primary care and improve the implementation of chronic disease management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 17 publications
1
49
0
7
Order By: Relevance
“…25,26 Nurses across all regulatory designations are extensively involved in activities related to chronic disease management. 10,11,[27][28][29][30][31][32][33][34][35] Our finding of a positive relation between the presence of 1 or more registered nurses in FHTs and clinical outcomes of patients with diabetes is consistent with results of studies conducted in other countries. 13,36 Similar findings have also been reported outside of primary care and within other disciplines.…”
Section: Discussionsupporting
confidence: 81%
“…25,26 Nurses across all regulatory designations are extensively involved in activities related to chronic disease management. 10,11,[27][28][29][30][31][32][33][34][35] Our finding of a positive relation between the presence of 1 or more registered nurses in FHTs and clinical outcomes of patients with diabetes is consistent with results of studies conducted in other countries. 13,36 Similar findings have also been reported outside of primary care and within other disciplines.…”
Section: Discussionsupporting
confidence: 81%
“…Across all of the studies the most common RN clinical responsibilities were: vaccinations,(Anderson et al, 2012, Condon et al, 2000, Halcomb et al, 2008, Lukewich et al, 2014, Pascoe et al, 2005, Phillips et al, 2009, Planas-Campmany et al, 2016, Todd et al, 2007, Walsh et al, 2015) ear syringe irrigation,(Anderson et al, 2012, Joyce and Piterman, 2011, Pascoe et al, 2005, Patterson et al, 1998, Todd et al, 2007, Walsh et al, 2015) dressing changes (Condon et al, 2000, Halcomb et al, 2008, Joyce and Piterman, 2011, Pascoe et al, 2005, Patterson et al, 1998), medication administration (Anderson et al, 2012, Halcomb et al, 2008, Joyce and Piterman, 2011, Patterson et al, 1998), removal of sutures (Pascoe et al, 2005, Patterson et al, 1998, Todd et al, 2007), venipuncture (Condon et al, 2000, Halcomb et al, 2008, Patterson et al, 1998), and first aid (Pascoe et al, 2005, Walker et al, 2015). Seven studies reported RN expertise in wound care as the task that was delegated to them by the primary care provider (Anderson et al, 2012, Condon et al, 2000, Halcomb et al, 2008, Joyce and Piterman, 2011, Lukewich et al, 2014, Phillips et al, 2009, Todd et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This understanding becomes more urgent as meeting the needs of an older and chronically ill population requires collaborative multi-disciplinary perspectives on providing patient care (Lukewich, Edge, VanDenKerhof, & Tranmer, 2014); which in turn will require nurses in general practice to participate more in clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%